2015
DOI: 10.5897/jcmr11.025
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems of street children in residential care in Zambia: Special focus on prediction of psychiatric conditions in street children

Abstract: This study aims to find out mental health problems and examine their role in prediction of psychiatric conditions in street children in residential care. Five (5) street children residential centres in Lusaka District, as well as a cross-section of street children (74) in residential care aged between 7 and 17 years were used for this study. Overall, 74 (68 males and 6 females) children in residential care were at risk of having a mental health problem. Forty of them were at risk of having multiple mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…Both of these earlier studies [ 28 , 29 ] examined school children and children from the general population. Compared to two other studies which used similar diagnostic interviews with street children and child labourers, the incidence of mental disorders in this study was still higher [ 30 , 31 ]. In one of these studies, which was conducted on 528 child laborers aged 5–15 years from Addis Ababa and which used the Diagnostic Interview for Children and Adolescents (DICA), the prevalence of any DSM-III-R childhood emotional and behavioural disorder was 20.1%.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Both of these earlier studies [ 28 , 29 ] examined school children and children from the general population. Compared to two other studies which used similar diagnostic interviews with street children and child labourers, the incidence of mental disorders in this study was still higher [ 30 , 31 ]. In one of these studies, which was conducted on 528 child laborers aged 5–15 years from Addis Ababa and which used the Diagnostic Interview for Children and Adolescents (DICA), the prevalence of any DSM-III-R childhood emotional and behavioural disorder was 20.1%.…”
Section: Discussioncontrasting
confidence: 60%
“…In one of these studies, which was conducted on 528 child laborers aged 5–15 years from Addis Ababa and which used the Diagnostic Interview for Children and Adolescents (DICA), the prevalence of any DSM-III-R childhood emotional and behavioural disorder was 20.1%. A cross-sectional study [ 31 ], using the Strength and Difficulties Questionnaire (SDQ), in 74 Zambian street children, 7–17 years old, found that 41% reported one mental health problem and 35% multiple problems. Despite being in the same age groups as these children, the street-working boys examined here are expected to be more severely burdened.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 41 , 42 Behavioural problems are documented mental health challenges of other minor categories of street children and there are gaps in the literature regarding behavioural problems among children on the street. 3 , 43 Therefore, it was enlightening to find children in this study who realised their misbehaviours towards their parents and worked on positive change. Additionally, street shopkeepers in this study had understudied the trajectories of behavioural problems of these children.…”
Section: Discussionmentioning
confidence: 99%